Classification and identification of karstic aquifers in the OSHTORANKUH region - Tayebeh KIANI; mohamad Fatholahzadeh (تحقیقات کاربردی علوم جغرافیایی)
The karst areas refers to individual areas that shaped by the dissolution of bedrock and subsurface drainage grid development and are connected mainly with limestone. The karstic formations outcrop 20 percent of the land surface of the planet is covered that 11 percent of Iran are part of this 20% is included. The ZAGROS region of origin karstic formations in the country that the formation of karst forms and numerous caves in the area attest to this claim. Overall creation and development of karst geomorphology, the formation of karstic aquifers are karstic systems. In fact karstic aquifers, underground reservoirs that store water in a web of interlocking joints and cracks, caves and canals. The karst can be effective ways to develop into three categories: physical, chemical and hydrogeologic studies divided that role of lithology and its properties, weather conditions and hydrological and structural factors such as faults and fissures, and slope area are of particular importance. In this study, characteristics OSHTORANKUH region of karst processes and the formation of karstic aquifers were examined and to do so using the AHP model the effect of weight each criterion was determined in karst area. Then, using the SAW model )is a subset of multiple criteria decision-making methods( Zoning areas prone to karstic aquifers OSHTORANKUH software was Arc GIS 10.3 and defining the center of the southern slopes of the western and north-eastern slopes of the mountain that are consistent with carbonate formation, the intersection of active faults and are the focus of surface runoff ,it also has a gentle slope than other parts of the region, have Better and more suitable conditions for the formation of karst processes karstic aquifers. The adaptation of the area most prone to the aquifer karst springs evidence of the correct zoning of the area is karstic aquifers.